English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

1 answers

Sin (a) / Sin (b) = Sin (a + b) / Sin (b - c)

Sin (a^2) / Sin (b^2) = Sin (a^2 + b^2) / Sin (b^2 - c^2)


Sin (a^2) Sin ( b^2 - c^2) = Sin (a^2 +b^2) Sin (b^2)
Sin (a^2) Sin (b^2) - Sin (a^2) Sin (c^2) = Sin (a^2) Sin (b^2) + Sin (b^2) Sin (b^2)
Sin (a^2) Sin (b^2) - Sin (a^2) Sin (c^2) = Sin (a^2) Sin (b^2) + Sin (b^2)^2
Sin (a^2) Sin (b^2) - Sin (a^2) Sin (b^2) = Sine (a^2) Sine (c^2) + Sin (b^2)^2
0 = Sine (a^2) Sine (c^2) + Sin (b^2)^2
- Sin (b^2)^2 = Sine (a^2) Sine (c^2)

2007-02-10 10:08:27 · answer #1 · answered by -=*QA*=- 2 · 0 2

fedest.com, questions and answers